Munca pe platformele digitale de livrare din România - Bădoi, Delia (Calitatea Vieții, 2020)
This paper shortly presents the research project “Employment strategies in the context of new vulnerabilities of the digitalisation process” GAR-UM-2019-XI-5.4-1, financed by the GAR-UM-2019 Romanian Academy Programme, 2019–2022.